Comprehensive power flow modelling of hierarchically controlled AC/DC hybrid islanded microgrids. (May 2021) - Agundis Tinajero, Gibran David; Nasir, Mashood; Vasquez, Juan C.; Guerrero, Josep M.
Highlights: Power flow modeling of controlled AC/DC microgrids in islanded operation mode. The control includes a primary and secondary for both AC and DC sides. The interlink converter includes primary and secondary control. The results are validated against Simulink. The introduced power flow models match with the time-domain solutions. Abstract: This paper presents the power flow modelling for AC/DC hybrid islanded microgrids including droop-controlled distributed generation units, secondary frequency and voltage restoration control for the AC side of the microgrid, and secondary voltage restoration control for the DC side of the microgrid. The interlink converter between the AC and DC microgrids includes a frequency-voltage droop control, and considers the effect of the secondary control for the AC microgrid side. Two case studies are presented for the power flow model evaluation, in the first case a microgrid with linear loads and equal droop characteristic for the distributed generation units are used; in the second case, voltage dependent loads for both AC and DC microgrids are included, and different droop characteristic are chosen for each distributed generation unit. Comparisons between the power flow solutions through the proposed modelling and the professional simulator MATLAB/Simulink are presented. Additionally, the computational speed and convergence rate of the power flow method are shown. The obtained results corroborate the reliability and effectiveness of the proposed power flow modeling to represent the controlled AC/DC hybrid microgrid including hierarchical controllers.